Komitmen Berorganisasi dan Persepsi tentang Keaktifan Berorganisasi pada Kader Perhimpunan Mahasiswa Katolik Republik Indonesia - Al Thuba Septa Priyanggasari; Deasy Christia Sera; Aina Widhiavani Rahmalita; Rinto Wahyu Widodo (Universitas Trunojoyo Madura, 2023)
The aim of this research was to measure the impact of organizational commitment on the perception of organizational activity among members of the Indonesian Catholic Student Association (Perhimpunan Mahasiswa Katholik Republik Indonesia or PMKRI). This study used a quantitative approach with correlational research design. The population in this study was the members of PMKRI Branch of Malang, who have been confirmed as members of PMKRI from the 2018 to 2020 academic years, with totaling 346 students. The sampling technique used in this study was non-probability sampling with an incidental sampling design, and a sample size of n = 110 students (32% of the population) was obtained. Data was collected using Likert scales, they were scale of perception of organizational activity which had reliability score 0,795 and scale of organizational commitment with reliability score 0,772, then analyzed using simple regression analysis. The results of this study indicate that there was a significant relationship between organizational commitment and the perception of organizational activity among members of PMKRI Branch of Malang. To improve organizational commitment, members can participate in organizational activities, take responsibility for their tasks, believe in the values of the organization, and remain loyal to the association. Additionally, the organization can evaluate the performance of its leaders and programs, and members and also leaders can work together to find solutions to improve the performance of the leaders and encourage members to become more active in the organization. For future research, it is recommended to expand the sample size and references to generalize the results to other branches of PMKRI.